2019
DOI: 10.4187/respcare.06271
|View full text |Cite
|
Sign up to set email alerts
|

Physiologic Effects of 3 Different Neonatal Volume-Targeted Ventilation Modes in Surfactant-Deficient Juvenile Rabbits

Abstract: BACKGROUND: Different brands of volume-targeted modes may vary the location of tidal volume (V T ) monitoring and whether peak inspiratory pressure is adjusted based on inspiratory, expiratory , or leak-compensated V T . These variables may result in different levels of support provided to patients, especially when an endotracheal tube (ETT) leak is present. We hypothesized that there would be no differences in gas exchange, triggering, or work of breathing between volume-targeted modes of 3 different brands o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Sample size calculation for surfactant treatment (n = 5 per group) was based on power analysis using mean and standard deviation of partial pres-sure of oxygen in the arterial blood (PaO 2 ) from a previous rabbit study that compared nebulized to directly instilled surfactant in intubated mechanically ventilated rabbits [22]. We included descriptive control animals (n = 2) that did not receive surfactant, based on our previous work with a similar animal rabbit injury model where disease severity was consistent up to 4 h following lung lavage [23]. Final sample size was determined as five animals per treatment group and two descriptive controls.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sample size calculation for surfactant treatment (n = 5 per group) was based on power analysis using mean and standard deviation of partial pres-sure of oxygen in the arterial blood (PaO 2 ) from a previous rabbit study that compared nebulized to directly instilled surfactant in intubated mechanically ventilated rabbits [22]. We included descriptive control animals (n = 2) that did not receive surfactant, based on our previous work with a similar animal rabbit injury model where disease severity was consistent up to 4 h following lung lavage [23]. Final sample size was determined as five animals per treatment group and two descriptive controls.…”
Section: Methodsmentioning
confidence: 99%
“…The FiO 2 was increased to 1.0, and the lungs were depleted of surfactant and injured by repeated lavage with 25 mL/kg of warmed (39 • C) normal saline (0.9%), with 5 min recoveries between lavages until dynamic compliance was 50% of the non-lavaged value or SpO 2 90-92% on FiO 2 of 0.5 [23]. The FiO 2 was reduced to 0.5 and animals were deemed surfactant-deficient when PaO 2 < 75 mmHg was confirmed with two consecutive ABGs 30 min apart following lavage/injury.…”
Section: Induction Of Surfactant-deficiency and Lung Injurymentioning
confidence: 99%
See 1 more Smart Citation
“…Several barriers have hampered the diffusion of volume-targeted ventilation, including provider experience level, lack of established V T targets based upon disease state, large endotracheal tube leaks (eg, > 50%), and a ventilator's ability to deliver and accurately measure V T . [77][78][79] Wong and colleagues 80 prospectively studied very low birthweight and ELBW subjects who underwent volumetargeted ventilation with the aim of describing breath-tobreath variation in expired V T . The authors analyzed 6 h of continuous ventilator data and found no significant variations in expired V T between cohorts, despite the ELBW cohort having significantly lower set V T (4.6 vs 7.2 mL, P < .001).…”
Section: Volume-targeted Ventilationmentioning
confidence: 99%
“…This study evaluated volume-targeted ventilation delivery in a single ventilator type because previous bench and animal studies have suggested considerable variability in ventilator performance, with variations in V T becoming more pronounced with increased leak or lower V T targets. 79,81 Future studies should evaluate V T target ranges for specific disease conditions, such as evolving RDS, congenital diaphragmatic hernia, meconium aspiration syndrome, and BPD, and incorporate performance data respective to different ventilators.…”
Section: Volume-targeted Ventilationmentioning
confidence: 99%